When dermatomyositis patient has blurring of vision – what goes wrong? - Ng, Christina Wei Khee; Hanizasurana H,; Nor Azita AT,; Nor Fariza N,; Zabri K, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Cytomegalovirus (CMV) retinitis occurs predominantly in Human Immunodeficiency Virus (HIV) -infected patients. It was also reported in HIV-seronegative patients with systemic autoimmune disorder requiring systemic immunosuppression, organ or bone marrow transplantation, haematological or breast malignancy receiving chemotherapy, ocular diseases following intraocular or periocular corticosteroid injection, diabetes mellitus and Good syndrome. However, CMV retinitis in patients with concurrent dermatomyositis and malignancy has not been previously reported. It has not been reported in cancer other than haematological or breast malignancy, or in cancer patient prior to chemotherapy. We report a case of 40-year-old HIV-seronegative woman with underlying dermatomyositis and lung malignancy who developed right CMV retinitis which relapsed after recommencement of immunosuppressant. Both episodes of CMV retinitis were successfully treated after taken her immunocompromised state into consideration.